Experience report of the contributions of telehealth in riverside communities of Amazonas in the pandemic - Jacqueline de Almeida Gonçalves Sachett; Isabela Cristina de Miranda Gonçalves; Waldeyde Oderilda Magalhães dos Santos (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to report on the creation and implementation of telehealth activities developed by the Forest Health Program in communities in conservation areas, in the state of Amazonas, during the COVID-19 pandemic. Methods: this is an experience report on the creation and implementation of the program. Results: the project began in June 2021 with medical and nursing services and currently has 63 points of connectivity installed. Dermatology was the most requested specialty (30.1%), with dermatitis being the main grievance diagnosed. For nursing, the most requested specialty was obstetrics, followed by pediatrics. Rio Madeira and the Catuá-Ipixema Extractive Reserve requested more than half of all consultations. Conclusion: this project showed a differentiated performance of telehealth in riverside communities in Amazonas, especially in the pandemic context, expanding health care in remote areas, such as these.